To Inhibit or Enhance? Is There a Benefit to Positive Allosteric Modulation of P2X Receptors? - Stokes, Leanne; Bidula, Stefan; Bibič, Lučka; Allum, Elizabeth (Frontiers in Pharmacology, 2020)
The family of ligand-gated ion channels known as P2X receptors were discovered several decades ago. Since the cloning of the seven P2X receptors (P2X1-P2X7), a huge research effort has elucidated their roles in regulating a range of physiological and pathophysiological processes. Transgenic animals have been influential in understanding which P2X receptors could be new therapeutic targets for disease. Furthermore, understandinghow inherited mutations can increase susceptibility to disorders and diseases has advanced this knowledge base. There has been an emphasis on the discovery and development of pharmacological tools to help dissect the individual roles of P2X receptors and the pharmaceutical industry has been involved in pushing forward clinical development of several lead compounds. During the discovery phase, a number of positive allosteric modulators have been described for P2X receptors and these have been useful in assigning physiological roles to receptors. This review will consider the major physiological roles of P2X1 - P2X7 and discuss whether enhancement of P2X receptor activity would offer any therapeutic benefit. We will review what is known about identified compounds acting as positive allosteric modulators and the recent identification of drug binding pockets for such modulators.